Students’physical fitness test in the the Faculty of Sport Science and Physical Education, National University of Laos - Phatsaphanh, Bounly; Sisomephou, Thongchanh; Keomueangsam, Khamla; Sayalath, Donmany; Thammavongsa, Sathaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research was to select the physical fitness test and evaluatestudents’ physical fitness in the Faculty of Sport Science and Physical Education, National University of Laos. The sample group used in this research was 157 students of in the Faculty of Sport Science and Physical Education, 42 of whom were females, by purposive sampling method in total students in the academic year 2022-2023. The approval letter was granted by the Executive Committee of Faculty of Sport Science and Physical Education, National University of Laos The research tools used in the data collection process included questionnaires and statistical tests. The statistics used in the data analysis include: Mean, Standard Deviation. Findings of the study showed as follows 1). The selection results for students’ physical fitness test of students in the Faculty of Sport Science and Physical Education reported a total of 10 male-female test items that were closely related with a value of R = 0.91 to 1. Therefore, all 10 test items were reliable and applicable. 2). From this study, it can be seen that the physical fitness of the male students of the Faculty of Sport Science and Physical Education compared to the total score of the test of 10 items with a total score of 100 points, which could be applied with a very good score of 3.6, equivalent to 26.6 percent at the good level, 55.06 percent at the middle level, 11.38 percent at the weak level and 3.4 percent at the very weak level. The physical fitness of female students in the Faculty of Sport Science and Physical Education compared to the total score of the test of 10 items with a total score of 100 points, which could be applied with a very good score of 1.9, 6.33 percent at the good level, 26.8 percent at the middle level, 63.81 percent at the weak level and 1.13 percent at the very weak level.